Students’ mental health and well-being during the COVID-19 pandemic. The role of psychological resilience and daily functioning. - Ioannidou, Louiza (Psychology Hub, 2023)
The present study examines how the COVID-19 pandemic affects college students' mental health and well-being. Furthermore, the study investigates the association between psychological resilience, daily functioning, and trajectories of mental distress during the COVID-19 pandemic. Our sample included 208 college students from a private University in Cyprus. Students completed the COVID-19 Functioning Scale, the Perceived Stress Scale, the Depression Anxiety Stress Scale, and the Connor Davidson Resilience Scale. Statistical analyses highlighted that COVID-19 perceived challenges negatively impacted students' mental health and well-being. In addition, results revealed that students with a higher level of resilience and a healthier daily routine and functioning indicate lower levels of perceived stress and mental difficulties. Study findings highlighted that high resilience and functioning could be protective factors for students' well-being during the pandemic. Thus, activities that foster resilience should be included in broader strategies to support students' mental health and well-being.